SPPK BURSA KERJA ASURANSI PADA PT SARANA LINDUNG UPAYA SEMARANG (Information Technology and Telematics, 2013)
In the world of the job fair a lot of the problems associated with a particular policy decision making regarding the selection of the workforce that need absolute employees in the company. In preparing for solving problems, managers saw the company as a system with the understanding of the company and identify sub-systems within the company.Goals to be achieved is to make the right decision support systems in order to help the PT. Means of protection efforts in the election Labor Semarang employees.The results in this study are based Insurance Jobs application decision support system can be used to help the PT Facility Protection Efforts Semarang in determining the right choice applicants based firestrength of applicants Keywords - SPK, Firestrength, Sarana Lindung Upaya